PENGARUH KEBIASAAN BELAJAR DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR SISWA EKONOMI KELAS X DI SMA KARTIKA 1 â 5 PADANG. - Defrianto, Defrianto; Afriza, Rina; Eprillison, Vivina (Pendidikan Ekonomi, 2014)
ABSTRACTÂ Â This research was conducted at the Padang 1-5 Kartika High School Study Habits Influence And Attention Parents Against Student Results X Class Economy In high school Kartika 1-5 Padang . The purpose of this study is to obtain empirical evidence about the Influence of Study Habits And Attention Parents Against Student Results X Class Economy In high school Kartika 1-5 Padang . The method used in this research is descriptive and associative . This research is a symptom , events and to determine the relationship between two variables or more , where the population sampled were used as much as 174 students out of a population of 308 students . Data habit learning ( X1 ) and parental concern ( X2 ) is obtained from the results of the questionnaire or questionnaires while economics student learning outcomes data ( Y ) is obtained from the documentation of the value of mid semester. Analysis of the data used in this study is a descriptive analysis and inductive analysis which consists of a normality test, multikolinielitas , heterosidasitas test , autocorrelation test , multiple regression analysis , determination ( R2 ) and test the hypothesis . The results of this study indicate that : 1 . Habit learning positive and significant effect on student learning outcomes economy class X SMA kartika 1-5 field , 2 . Attention parents and significant positive effect on learning outcomes of students high school economics class X kartika 1-5 padang , 3 . habit learning and parental concern and a significant positive effect jointly to the results of the economic study of high school students kartika 1-5 padang . Based on these results , it is suggested that students , parents , teachers and school authorities to pay more attention to another study habits and attention of parents in the learning process in an effort to further optimize student learning outcomes economy class X SMA kartika 1-5 padang.